2022
DOI: 10.3122/jabfm.2022.04.210462
|View full text |Cite
|
Sign up to set email alerts
|

Patient Barriers to Accessing Referred Resources for Unmet Social Needs

Abstract: Introduction: Many primary care clinics screen patients for their unmet social needs, such as food insecurity and housing instability, and refer them to community-based organizations (CBOs). However, the ability for patients to have their needs met is difficult to evaluate and address. This study explores patient-reported barriers to accessing referred resources using a conceptual framework that identifies opportunities for intervening to optimize success.Methods: Patients who participated in a social needs sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Our work has resulted in four student-led, peer-reviewed publications and eight presentations at state, national, international conferences focused on the development and implementation of the Help Desk model, adaptations of the program during the pandemic, evaluating factors associated with a successful patient referral, and patient-reported barriers to accessing referred resources ( 15 17 , 29 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our work has resulted in four student-led, peer-reviewed publications and eight presentations at state, national, international conferences focused on the development and implementation of the Help Desk model, adaptations of the program during the pandemic, evaluating factors associated with a successful patient referral, and patient-reported barriers to accessing referred resources ( 15 17 , 29 ).…”
Section: Resultsmentioning
confidence: 99%
“…This intervention has the potential to provide a valuable touch point for patients seeking to navigate a complex and often fragmented system of health and social services. For patients, SMS text messaging may be a convenient, affordable, and accessible modality to deliver information and reminders about referred services, improving upon solely verbal dissemination methods that create patient-reported approachability barriers (eg, forgetting about resources and lacking the necessary information to connect) [ 12 ]. If feasible and acceptable to patients, SMS text messaging may also offer a scalable means of increasing contact between patients and their care teams without overextending organizational capacity, allowing providers to direct their case management efforts to those cases where more intensive approaches would be most valuable.…”
Section: Discussionmentioning
confidence: 99%
“…During these meetings, frontline clinical stakeholders relayed patient requests for the incorporation of SMS into the existing social needs program. The potential benefits of an SMS text message–based intervention were further bolstered by studies of patient-reported barriers [ 12 ] and low proportions of resource connection (33%) [ 10 ] at the FQHC. With stakeholder support, a convenience sample of 16 patients was surveyed about SMS text messaging during navigator follow-up calls: 87.5% of patients stated that they were comfortable with receiving SMS text messages about referred social needs resources, and 56.3% of them even preferred to receive this information via SMS text message rather than by telephone or in person.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The wording of screening questions and the amount of paperwork involved, along with mistrust, perceived stigma, and negative prior experiences seeking resources disproportionately pose barriers to engagement with clinic‐based screening and referral for people of color and historically marginalized groups (Spain et al, 2021; Pfeiffer et al, 2022; Ronis et al, 2022). Service access poses its own set of inequities (Gadson et al, 2017; Lee & Rispoli, 2017; Sandhu et al, 2022). Identifying practices and strategies to support healthcare and early childhood partners to screen and coordinate service provision in different clinic and community contexts can inform the future efforts to spread and scale clinic‐based approaches to mitigating health disparities and addressing negative SDH.…”
Section: Introductionmentioning
confidence: 99%